2014
DOI: 10.1111/jop.12159
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ALDH1, CD44, OCT4 and SOX2 in tongue squamous cell carcinoma and their association with disease progression and prognosis

Abstract: Taken together, these data suggest that the stem cell markers ALDH1, CD44, OCT4 and SOX2 are closely related in TSCC, and the expression of SOX2 can be used as a prognostic indicator of TSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
2
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 36 publications
(44 reference statements)
9
90
2
16
Order By: Relevance
“…[ [15][16][17][18] Etiological differences may have contributed to this result. In addition, majority of the tumors in the present study sample contained buccal mucosal cancers; while the literature quoted above have focused on tongue cancers.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…[ [15][16][17][18] Etiological differences may have contributed to this result. In addition, majority of the tumors in the present study sample contained buccal mucosal cancers; while the literature quoted above have focused on tongue cancers.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, majority of the tumors in the present study sample contained buccal mucosal cancers; while the literature quoted above have focused on tongue cancers. [16,18] Furthermore, Sox-2 expression has been shown to be related to poor survival at sites such as esophagus and bladder as well. [19,20] In addition, problems highlighted below concerning survival data may have also contributed to this result.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not in agreement with the results of this study showing that CD44 and CD44v9 were abundantly expressed in OSCC. Many reports investigated the CD44 expression rate (50~80%) and relationship between CD44s expression and clinicopathological factors (28,29). However, the results of these studies have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that the SOX2 proteins were overexpressed in the TSCC, and demonstrated that SOX2, recurrence and distant metastasis were independent prognostic factors of overall survival in patients with TSCC. Therefore the studies concluded that the expression of SOX2 may be used as a prognostic indicator of TSCC (82). SOX2 was exclusively expressed in the CSCs of OSCC patients and the expression of SOX2 was significantly associated with a poor prognosis of OSCC and lymph node status, which indicates the potential prognostic value of SOX2 in OSCC.…”
Section: Sox2 In Osccmentioning
confidence: 99%